APPLICATION OF EDUCATIONAL TECHNOLOGY IN MANAGEMENT CONTEXT: OPPORTUNITIES AND CHALLENGES - Rhomadoni, Mohamad Fadeli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is intended so that the application of technology in the world of education can be implemented well as an opportunity to face the challenges of the digital era. By using the research method approach used in this article is qualitative. This research was carried out at MI Islam Fitriyah Banjarwaru Lumajang. Digital transformation has become something important as a discussion sector related to the world of education. For educators, there are also obstacles that must be resolved, including moral crises, digital literacy skills, social crises, developments in science and technology, being role models and the use of technology-based learning media. The importance of applying technology in education is to facilitate learning and improve the quality of effective and efficient learning performance. Improving quality in order to prepare digitally literate human resources is a necessity that must be maximized so that learning can be carried out efficiently and optimally. The use of social media in education is really needed, because it is a trigger for students to learn because they tend to be more interested in learning on social media than reading books, which on social media appear more interesting than books. The use of media platforms as teaching and learning activities can be done in several ways with various types of platforms that can be used such as multimedia, electronic media, computers, internet print media, audio-visual media and visual media.